Ensaio clínico fase III para avaliação da eficácia terapêutica de um medicamento fitoterápico contendo FSP1001, ALS1002, CRT303, em paciente com transtorno de ansiedade leve ou moderada. - Leite, Ana Lourdes Almeida e Silva (2017)
The phase III trial aims to compare the new treatment to the standard treatment available for the same medical condition. The analysis of the data obtained at this phase may lead to the registration and approval by the health authorities for the commercial use of the new drug or procedure. FSP1001. As a herbal remedy it is traditionally used as a sedative and anxiolytic. Several preclinical studies have been performed to prove its safety and tolerability, as well as to clarify its pharmacological activities. This study aims to evaluate the therapeutic efficacy of a herbal medicine containing FSP1001, ALS1002, CRT303, in patients with mild and moderate anxiety disorder and for this purpose it adopted the Hamilton Anxiety Scale HAM-A. An open, double-blind monocentric study was performed with 110 volunteers of both sexes.Patients included were randomly assigned to one of two treatment groups: Group A (test drug) - 1 tablet of the combination of FSP1001 (100mg), CRT303 (30mg) and ALS1002 (100mg) in combination To 1 tablet of placebo; Group B (reference drug) - 1 placebo tablet associated with 1 tablet ARLA504 (50mg). The results of the evaluation of the adverse events show that the association of FSP1001, CRT303, and ALS1002 was well tolerated and that it is safe to use in the dosages tested. The analysis of primary efficacy (mean alteration of the HAM-A anxiety score) and secondary efficacy, highlighting the responsive and remission data of the disease, suggest that the formulation studied presented promising results as a therapeutic option in the action against anxiety.